Contingent valuation a critical assessment - Hausman, Jerry A. (Contributions to economic analysis, 1993)
The papers in this volume present a critical assessment of contingent valuation (CV). CV is a survey method that attempts to estimate individual values for economic goods by asking people hypothetical questions about their willingness to pay for such goods. The text reports research which is mainly from economists with specialities in economic theory, econometrics and public finance, rather than from the more narrowly focused research of environmental economics. The research of specialists in psychology, market research and litigation is included.